Reef Island Evolution and Dynamics: Insights from the Indian and Pacific Oceans and Perspectives for the Spermonde Archipelago - Kench, Paul S.; Mann, Thomas (Frontiers in Marine Science, 2017)
Along southwestern Sulawesi, Indonesia, the Spermonde Archipelago comprises some 120 islands of variable size and degree of anthropogenic modification. Comparable to adjacent areas in Southeast Asia, the Spermonde Archipelago is characterized by the congregation of a naturally high marine biodiversity and, at the same time, a high population density influencing the surrounding environmental conditions. As a consequence, during the last decades, research projects that have been carried out in the Spermonde mainly focused on social, ecological, political and economic interactions. However, geological and geomorphological aspects of the coral reef islands are less well understood and there have been few studies undertaken since the pioneering work of Umbgrove, Kuenen and Verstappen in the Indonesian archipelago in the early to mid-20th century. Here we review the existing studies, with a focus on the Spermonde Archipelago, and reconcile them with more recent works on reef island evolution and dynamics from the Indian and Pacific Oceans. This synthesis shows that reef islands in the Spermonde Archipelago are well suited for geomorphological investigations, and provides perspectives for future reef island research in that area that will have global interest. We identify four research priorities: 1) To identify the timing and chronology of island formation; 2) Improved understanding of carbonate budgets and sediment generation that contribute to island building; 3) Document morphological changes in reef islands at seasonal to decadal timescales, and; 4) Quantify the process regime that drives sediment transport and island change with particular focus on the role of different monsoon seasons.